Analysis Of Local Awareness And Revitalization Of Angkola's Mangupa Traditions - Akhiril Pane (CV. AFDIFAL MAJU BERKAH, 2022)
The purpose of this study was to determine the local wisdom of the mangupa tradition of the Angkola customary community. The research method used in this research is qualitative research. Next, collect data that will be inventoried, selected, grouped, analyzed, interpreted, and then concluded. This data collection was carried out by conducting structured interviews in a structured list of questions and structured observation. The data analysis technique was carried out by means of research data transcription, after the recorded data were transcribed into text, the research data was then translated into Indonesian. Then the data in this study are classified based on the need for analysis and research work steps. The results of this study found that the local wisdom of the mangupa tradition is seen as an interaction between deep-rooted traditional customs and the beliefs of the Angkola customary community on traditions that have lived from generation to generation. Religious values ​​that show respect for the Creator are respected for the audience showing politeness in language and humility which is embodied in the Angkola customary mangupa tradition. The aesthetic values ​​of humility and respect show the values ​​of local wisdom, politeness, and respect for traditional leaders and the traditional Angkola community.